STRUCTURAL CHANGES AND REGIONAL MODELS OF AGRICULTURE - J. Doitchinova (Trakia Journal of Sciences)
More than 10 years of Bulgarian membership in the European Union has resulted in significant changes not only in the product and organizational structures of the agrarian sector. These changes take place at different speed and form new models of agriculture by country. The purpose of the article is to analyze the regional changes in the product and organizational structures and to assess the characteristics of the emerging agricultural models in the northern and southern planning regions of Bulgaria. The thesis of the article is that, regardless of the unidirection of the changes, the agrarian identity of the regions affects their speed and their characteristics. The methdological approach is based on the assessment of the changes in product and organizational structures and their impact on the development of the regions. Subject of the research is the agrarian sector in the planning regions in our country. Conclusions were made for the consequences of changes in the importance of agriculture for the regional economy, their environmental impacts, income from farming, jobs, changes in the population, etc. The characteristics of agricultural models are described and guidelines and possibilities for their adaptation and development of the regional agricultural production potential were developed.